Trends in Heart Transplantation and Outcome Analysis: Nationwide Study Using the National Inpatient Sample and Readmission Database - Vivek Joseph Varughese; Aditya Sunil Bhaskaran; Hadrian Hoang-Vu Tran; Nikita Wadhwani; Vignesh Krishnan Nagesh; Izage Kianifar Aguilar; Damien Islek; Simcha Weissman; Adam Atoot (Medical Sciences)
Background: Heart transplantation (Htx) remains the definitive therapy for patients with end-stage heart failure. Despite advancements in mechanical circulatory support (MCS), immunosuppressive strategies, and organ allocation policies, donor availability remains a major limitation. This study analyzes the trends in Htx in the United States between 2016 and 2022, focusing on demographic shifts, mortality trends, and 30-day readmission patterns. Methods: We utilized the National Inpatient Sample (NIS) from 2016 to 2022 and the National Readmissions Database (NRD) for 2021 to identify Htx admissions using ICD-10 PCS code O2YA0Z0. Patient characteristics, mortality rates, and readmission patterns were analyzed using ANOVA and multivariate logistic regression, with statistical significance defined as p < 0.05. Results: The total number of Htx procedures increased from 641 in 2016 to 773 in 2022. The mean age of transplant recipients remained between 45 and 50 years, with no significant differences across years. Racial and socioeconomic disparities persisted, with approximately 60% of transplants occurring in White patients and 21–26% of recipients belonging to the lowest income quartile. All-cause in-hospital mortality remained stable at 4–7%. The 30-day readmission rate in 2021 was 57.7%, with heart failure, transplant rejection, and infections being the leading causes. Peripheral vascular disease (PVD) was the only comorbidity significantly associated with higher 30-day readmission risk (OR: 1.815, 95% CI: 1.477–2.230). Conclusions: Htx utilization has increased over time, driven by improvements in donor allocation and perioperative management. However, racial and socioeconomic disparities remain, and readmission rates continue to be high. Future efforts should focus on optimizing post-transplant care and addressing disparities to improve long-term outcomes.